2017
DOI: 10.21521/mw.5763
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy of systematic karyotype evaluation of cattle qualified for reproduction

Abstract: Diagnostyka cytogenetyczna umożliwia identyfikację i wczesną eliminację z hodowli zwierząt obarczonych dziedzicznymi wadami kariotypu, powodującymi zaburzenia rozwoju oraz znaczące obniżenie wskaźników płodności (od kilkudziesięciu do 100%) i produkcyjności stad hodowlanych, a w konsekwencji wymierne straty finansowe. Ze względu na potencjalną możliwość spontanicznego pojawiania się aberracji chromosomowych i szybkiego rozprzestrzeniania się tych wad genetycznych w populacji, zwłaszcza w warunkach stosowania s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Most genetic testing performed in breeding programmes has stressed genomic evaluation of bulls (Jennings et al, 2020), while relatively little attention is given to cytogenetic testing. Most often, cytogenetic screening tests are performed to identify chromosomal aberrations in young bulls before they are determined to be qualified for reproduction (Kozubska‐Sobocińska & Danielak‐Czech, 2017). Karyotype monitoring, including identification of chromosomal instabilities, enables culling of animals with chromosomal abnormalities, as well as assessment of the fertility of even young animals, as these instabilities can have harmful effects on future pregnancies (Jennings et al, 2020; Selvan et al, 2021; Tutt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most genetic testing performed in breeding programmes has stressed genomic evaluation of bulls (Jennings et al, 2020), while relatively little attention is given to cytogenetic testing. Most often, cytogenetic screening tests are performed to identify chromosomal aberrations in young bulls before they are determined to be qualified for reproduction (Kozubska‐Sobocińska & Danielak‐Czech, 2017). Karyotype monitoring, including identification of chromosomal instabilities, enables culling of animals with chromosomal abnormalities, as well as assessment of the fertility of even young animals, as these instabilities can have harmful effects on future pregnancies (Jennings et al, 2020; Selvan et al, 2021; Tutt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Silver foxes had a more stable genome than blue foxes and hybrids. Vaneste et al [41], Alfarawati et al [42], Kozubska-Sobicińska, and Danielak-Czech [43] attribute reproductive failure to Robertsonian translocation, among other factors. Although the animals have a normal phenotype, they are affected by impaired fertility, oestrous cycle disturbances, and an extended inter-birth interval.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary research has shown that this method is highly useful for diagnosing submicroscopic chromosomal rearrangements (impossible to detect with common cytogenetic tools), which may increase the detectability of reciprocal translocations, of which the frequency in the populations is probably much higher than previously estimated. For this reason, it seems especially justifiable to use this research tool prophylactically to assess the karyotypes of elite boars in AI centers (Table 1) [7,14,31,94].…”
Section: Cytomolecular Diagnosticsmentioning
confidence: 99%
“…The highest effectiveness of these activities will be ensured by the early prevention of cytogenetic defects based on the general principle of qualifying those young animals for breeding herds, which are screened for karyotype normality before their reproductive use [4,12]. In some countries, identification of chromosomal aberration carriers and their elimination from breeding is an established standard or a legal obligation arising from the implementation of tasks related to the organization of farm animal breeding and reproduction and from sire evaluation and selection programs to ensure planned breeding progress [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%